Emerging international regime of information security - S. V. Shitkov; T. A. Polyakova; A. A. Smirnov (Vestnik MGIMO-Universiteta)
The article examines burning issues of the formation of an international regime in the field of ensuring international information security in the context of geopolitical transformations and turbulence. The theory of international regimes developed by Russian and foreign researchers is used as a theoretical and methodological basis for the study.Based on the classical definition of the international regime, the authors focus on the norms and principles in the field of international information security. The norms and principles in the field of international information security as the rules of responsible behavior in the global information space were first proposed by Russia and its SCO partners in 2011 as part of a discussion of the UN General Assembly. However, Russian initiatives met with resistance from the United States, resulting in a fragmentation of the existing regulatory regime in the field of international information security. Currently, the relevant norms and principles, which are based on the fundamental principles of international law, enshrined in the UN Charter, are presented in the resolutions of the UN General Assembly, and are also enshrined in the reports of the Group of Governmental Experts on achievements in the field of informatization and telecommunications in the context of international security.The norms fixed in the documents are not mandatory, but they make an important contribution to ensuring international stability by structuring the expectations of various actors in the field of information security. However, the lack of formal consolidation and institutionalization of these norms within the framework of international treaties reduces their legitimacy.